coolio
![t_1=11](https://img.qammunity.org/2019/formulas/mathematics/high-school/gu5mumjjizavn84kmh33i21gioxl20jx39.png)
![t_n=t_(n-1)-13](https://img.qammunity.org/2019/formulas/mathematics/high-school/irs4mpxqd3vizd3p3jba3fk46nyar2j8yc.png)
so each term is ound by subtracting 13 from the previous term
an aritmetic sequence can be written as
were
is the nth term
is the first term
d is common difference, which can also be found by doing
![t_n-t_(n-1)=d](https://img.qammunity.org/2019/formulas/mathematics/college/2xzqd77cks5imke7mjxa36nptb2aczjd9e.png)
n=wich term
we know that
and we can find d
,
![t_n-t_(n-1)=-13=d](https://img.qammunity.org/2019/formulas/mathematics/college/5l36cu0uazq1ks5x0rd0eu9z1xdic7ocii.png)
so te general term is
which can also be expanded and written as
![t_n=-13n+24](https://img.qammunity.org/2019/formulas/mathematics/college/5jed69jbvi8dzzoq8x7wzqvzq3pifkn6og.png)